Abdominal Cocoon Syndrome: A Case Report - Rahman, Meher Angez; Hasan, Mizanul; Hj Sulaiman, Nurfizah Nadiah Binti (International Journal of Scientific Research and Management (IJSRM), 2025)
Abdominal cocoon syndrome (ACS) is defined as idiopathic partial or total encapsulation of the bowel and other abdominal organ within a fibrocollageneous membrane and considered as a rare cause of small bowel obstruction (1). Also known as primary sclerosing encapsulating peritonitis (SEP).  The presence of fibrous membranes that encompasses the intestines forming a sort of butterfly cocoon. Patients often present with symptoms of partial intestinal obstruction, which is challenging to diagnose before laparotomy. Of all the available investigations, the contrast-enhanced computed tomography of the abdomen is the most sensitive, showing a sac like fibrous membrane covering the bowel loops along with the fluid collection. Definitive treatment includes excision and adhesiolysis.